1909 Idaho Sess. Laws 55 - (:unkn) unknown (My University, 1909)
An Act to Define the Crime of Burglary with Explosives and Providing the Punishment Therefor, and Declaring an Emergency, § 1: Enhanced the sentence of any person who, with intent to commit crime, breaks and enters into any building, and attempts to open any vault, safe, or other secure place within said building by using nitro-glycerine, dynamite, gunpowder, or any other explosive, shall be deemed guilty of burglary with explosives. Violators imprisoned for a period of not less than ten, nor more than twenty-five years.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME